Final Year Project Supervisor Management System - MEENAKSHI, KANNAN (Universiti Malaysia Sarawak (UNIMAS), 2019)
The Final Year Project (FYP) is the culmination of degree for undergraduate student because through this project, the undergraduate student will be able to propose any project or research based on their skills and knowledge gained throughout their study. Furthermore, the FYP will test undergraduate student ability in many aspects such as to propose, design, develop, and evaluate quality system, make research based on their selected field, make good decisions, and overcome limitation and constraints in developing project. In University Malaysia Sarawak (UNIMAS), the completion of FYP is one of the listed requirements for undergraduate final year student to graduate. Therefore, each student need a lecturer as their supervisor to guide them during the FYP. The potential supervisor can be any available lecturer that have not exceed their quota for supervision. Moreover, both student need to have a good collaboration with their supervisor to develop a welldeveloped project. Therefore, it is not an easy task to search for a potential supervisor because many student face obstacles in finding themselves the potential supervisor. In conjunction, the Final Year Project Supervisor Management system is proposed to recommend the potential supervisor for the student through the system by displaying the potential supervisor information. This information purpose is to help the student to gain some basic information about the potential supervisor before they proceed with their request for supervision.